Case Based Learning In Biochemistry - USHA ADIGA; SACHIDANANDA ADIGA (International Journal of Pharma and Bio Sciences, 2011)
Background: Case based learning (CBL) is a popular method of teaching in medical schools. The primary aim of implementing CBL in to the curriculum of medical schools is to expose the students to the real world problems and to prepare them to analyze, interpret and solve them. The objective of our study is to find the effectiveness of CBL compared to routine didactic lectures and to know whether CBL can be adopted as a regular method of learning in biochemistry curriculum. Methodology: In addition to didactic lectures, CBL was used as learning method in few topics like heme metabolism in fourth and lipoprotein metabolism in third semester exclusively. The effectiveness was assessed by comparing the post CBL and post lecture scores. Students’ perception was assessed by a questionnaire which is validated by peers. Results: Mean scores were 67.3±1.8% and 65.7±1.7%, post CBL and post lecture respectively for the fourth semester and 76.1±1.2% and 74.3±1.9% respectively for third semester.P<0.001 suggested that post CBL grades were extremely significantly higher in both the semesters. Majority of the students (54%) opined that the case was appropriate and useful. 41% students found this method of learning very difficult.